2014
DOI: 10.1158/1541-7786.mcr-13-0419
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 Targets 15-PGDH and Promotes Cholangiocarcinoma Growth

Abstract: MicroRNAs (miRs) are a group of small, non-coding RNAs that modulate the translation of genes by binding to specific target sites in the target mRNA. This study investigated the biological function and molecular mechanism of microRNA-21 (miR-21) in human cholangiocarcinoma. In situ hybridization analysis of human cholangiocarcinoma specimens showed increased miR-21 in cholangiocarcinoma tissue compared to the non-cancerous biliary epithelium. Lentiviral transduction of miR-21 enhanced human cholangiocarcinoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…A study using human CCA specimens has revealed elevated miR-21 expression in the CCA tissue compared with noncancerous biliary epithelium. This study has also demonstrated that overexpression of miR-21 promotes CCA growth by targeting the key enzyme for prostaglandin conversion, 15-hydroxyprostaglandin dehydrogenase (15-PGDH) [39]. These studies support the notion that miR-21 may be another strong candidate biomarker in liver pathology.…”
Section: Strong Candidate Biomarkers For Liver Diseasessupporting
confidence: 57%
“…A study using human CCA specimens has revealed elevated miR-21 expression in the CCA tissue compared with noncancerous biliary epithelium. This study has also demonstrated that overexpression of miR-21 promotes CCA growth by targeting the key enzyme for prostaglandin conversion, 15-hydroxyprostaglandin dehydrogenase (15-PGDH) [39]. These studies support the notion that miR-21 may be another strong candidate biomarker in liver pathology.…”
Section: Strong Candidate Biomarkers For Liver Diseasessupporting
confidence: 57%
“…In addition, studies of human colorectal cancer tissue have shown that MIR21 is upregulated in colorectal cancer cells, and that tumor MIR21 expression level is associated with high-level expression of the genes involved in inflammatory responses and worse clinical outcome (15, 16). MIR21 appears to downregulate gene products that catalyze degradation of PGE 2 , which leads to increased level of PGE 2 in the tumor microenvironment and promotes tumor growth in a xenograft model (17). Hence, there might be a synergistic effect of MIR21 and PTGS2 on tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…miR-21 is highly up-regulated in hypoxia and plays an important role in cell growth and proliferation [13]. miR-21 is involved in various pathological and physical processes, inhibiting inflammation and apoptosis via down-regulation of target genes [14][15][16][17][18]. miR-21 plays a number of roles in solid cancers [19].…”
Section: Introductionmentioning
confidence: 99%